2008
DOI: 10.1530/eje-08-0213
|View full text |Cite
|
Sign up to set email alerts
|

Cabergoline and the risk of valvular lesions in endocrine disease.

Abstract: Aims: The cardiac valvular risk associated with lower exposure to cabergoline in common endocrine conditions such as hyperprolactinemia is unknown. Methods and results: We performed a cross-sectional, case-control echocardiographic study to assess the valvular status in 102 subjects receiving cabergoline for endocrine disorders and 51 matched control subjects. Cabergoline treatment ranged from 12 to 228 months, with a cumulative dose of 18-1718 mg. Valvular regurgitation was equally prevalent in both groups an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
84
2
7

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(102 citation statements)
references
References 24 publications
9
84
2
7
Order By: Relevance
“…Several studies in patients with Parkinson's disease have shown an association between treatment with pergolide or cabergoline and an increased mitral tenting area (1,23,24). In patients treated for prolactinoma, only Lancellotti et al measured the mitral tenting area, and reported a significantly increased area in patients treated with cabergoline, and, moreover, an association of increased area with more severe mitral regurgitation (10). An increase in mitral tenting area might be an early sign of alterations of cardiac valve structure, and this measurement should be included in future echocardiographic studies in prolactinoma patients.…”
Section: Cabergoline and Cardiac Valve Disease: Prolactinoma Versus Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies in patients with Parkinson's disease have shown an association between treatment with pergolide or cabergoline and an increased mitral tenting area (1,23,24). In patients treated for prolactinoma, only Lancellotti et al measured the mitral tenting area, and reported a significantly increased area in patients treated with cabergoline, and, moreover, an association of increased area with more severe mitral regurgitation (10). An increase in mitral tenting area might be an early sign of alterations of cardiac valve structure, and this measurement should be included in future echocardiographic studies in prolactinoma patients.…”
Section: Cabergoline and Cardiac Valve Disease: Prolactinoma Versus Pmentioning
confidence: 99%
“…After the publication of the papers, which showed an increased risk of valve regurgitation after treatment with pergolide and cabergoline in patients with Parkinson's disease, six cross-sectional studies have evaluated the association between valve regurgitation and the use of cabergoline in patients treated for prolactinoma, including the study by Wakil et al published in this edition of the European Journal of Endocrinology (Table 1) (10)(11)(12)(13)(14)(15). These studies included a total of 413 patients, treated with cabergoline for 45-79 months.…”
Section: Introductionmentioning
confidence: 99%
“…Cabergoline, which possesses a complete 5HT 2b agonistic activity, is the drug of choice in the treatment of prolactinomas, but the results of observational studies investigating the risk of FVHD in these patients are still controversial. Some of them have reported no relevant findings (8,9,10,11,12), five trials have observed clinically insignificant valvular changes (13,14,15,16,17), and only one study has reported an increased prevalence of moderate tricuspid regurgitation with a cumulative dose-dependent risk (18). Published data on the potential profibrotic effect of bromocriptine, a partial 5HT 2b agonist, are exclusively limited (19).…”
Section: Introductionmentioning
confidence: 99%
“…Soon after the 2007 NEJM publications on this topic [1,2], many centers analyzed echocardiographic results in cross-sectional studies among patients with pituitary disease treated for hyperprolactinemia and/or prolactinomas with cabergoline [7][8][9][10][11][12][13][14][15]. None reported clinically significant valvular heart disease [8][9][10][11][12][13][14][15] with the single exception in a cohort with a high rate of background hypertension [7] and for which the prospective follow up of this cohort receiving ongoing cabergoline therapy, failed to show progressive * Lisa B. Nachtigall lnachtigall@mgh.harvard.edu disease [16].…”
mentioning
confidence: 99%
“…None reported clinically significant valvular heart disease [8][9][10][11][12][13][14][15] with the single exception in a cohort with a high rate of background hypertension [7] and for which the prospective follow up of this cohort receiving ongoing cabergoline therapy, failed to show progressive * Lisa B. Nachtigall lnachtigall@mgh.harvard.edu disease [16]. While the preliminary cross-sectional data were essentially negative, including mean cumulative doses in these studies that ranged from 146-443 mg [7][8][9][10][11][12][13][14][15], long term randomized prospective studies have recently become available [16][17][18] and the one by Vroonen et al in this issue is the longest in duration with a median interval between echocardiograms of 62.5 months and a median total duration of therapy with cabergoline of 124.5 months, and this study was unique, among the prospective studies, by virtue of the inclusion a control group of non cardiac patients at baseline [18]. The prospective randomized controlled study by Vroonen et al from CHU Liège in Belgium, reported in this issue of Endocrine, is reassuring in the lack of clinically relevant valvular heart disease seen in pituitary patients treated with typical doses of dopamine agonists [18] and confirms similar findings among patients with prolactin disorders prospectively evaluated [16,17] as well as a prior prospective study among patients treated for acromegaly [19].…”
mentioning
confidence: 99%